Eight new species of Megaselia Rondani (Diptera: Phoridae) from the United Arab Emirates, Oman, and Yemen - Disney, R. Henry L. (Zootaxa, 2006)
The following new species of Megaselia are described from the United Arab Emirates, with four of these also recorded from additional countries (indicated in brackets). M. ebejeri (Oman), M. floccicauda (Yemen), M. gallagheri (Oman), M. multivesiculae, M. necmera, M. nudihalterata (Oman, Yemen), M. papei and M. quintincisa.